Group Investigative Learning Model to Improve Students' Critical Thinking Skills Through Learning Social Sciences - Esty Setyo Utaminingsih; Sulasih Sulasih; Tri Mulyaningtiyas (Edueksos: Jurnal Pendidikan Sosial & Ekonomi, 2023)
ABSTRACT The fourth-grade elementary school students have not been able to construct the information they get well, so their critical thinking skills are still not good. This research aims to study the role of the learning models’ investigation group in elementary school through critical thinking skills in social science learning. The method used in a study is a literature review. Data collection techniques through collecting articles on the group investigation model, critical thinking, and learning Social Sciences in elementary schools. Databases used for journal searches include Google Scholar, Research Gate, Academia Edu, and Publish or Perish. The research results show that the group investigative learning model guides students to identify information or problems, explore information, make knowledge a provision, analyze data, and construct knowledge to find solutions to problems. Then conclude. These activities lead students to train and familiarize students with thinking critically. Critical thinking is one of the skills that students must have in 21st-century learning. The group investigation learning model is essential in improving students’ critical thinking skills in learning social studies in elementary schools in 21st-century education.Keywords: Critical Thinking, Group Investigation, Social Science